Tahsin Al-Qur'an Learning Method in Improving Al-Qur'an Reading Ability at Madrasah Aliyah Nurul Iman Betara Tanjab Barat Jambi - tina, Martina Wulandari (EDUCAN : JURNAL PENDIDIKAN ISLAM, 2024)
This paper aims to explore and analyze the tahsin Al-Qur'an learning method used at Madrasah Aliyah Nurul Iman, Betara Tanjab Barat, Jambi, and its impact on improving students' ability to read the Al-Qur'an. This research was conducted using a qualitative approach using the case study method. Data was collected through observation, interviews and analysis of documents related to the curriculum and learning materials. The research results show that Madrasah Aliyah Nurul Iman has implemented various methods of learning Al-Qur'an tahsin which involve teaching the rules of recitation, pronunciation, and understanding the text of the Al-Qur'an. This method includes the use of experienced teachers, relevant learning materials, and various interactive learning techniques. The impact of applying this method is to increase students' ability to read the Al-Qur'an, which is reflected in their ability to pronounce the Al-Qur'an text well, understand the meaning of the text, and apply the rules of recitation correctly. This research concludes that the tahsin Al-Qur'an learning method at Madrasah Aliyah Nurul Iman has been successful in improving students' ability to read the Al-Qur'an. However, it needs to continue to be improved with a more contextual approach, including the integration of technology and innovative learning methods to answer the demands of the times. It is hoped that the results of this research can provide guidance for madrasas and other Islamic educational institutions in improving the quality of Al-Qur'an tahsin learning.